The Islamic Defenders Front (FPI) As an Opposition Force in The Joko Widodo’s Era in 2014-2020 - Reni Rentika Waty (International Journal of Islamic Khazanah, 2021)
FPI (Islamic Defenders Front) is a mass organization that has consistently positioned itself as the opposition since the reformation. However, during the Jokowi era, the FPI's opposition was more dominant than during before Jokowi era. Using Robert A. Dahl's opposition theory and Maurice Duverger's pressure group theory, as well as qualitative methods, this study wants to see the reasons for FPI as an opposition, FPI's affiliation with Joko Widodo's political opponents. It then analyzes the relationship between ideological and political aspects. This study shows that the FPI oppositional movement is divided into two. That is, the FPI oppositional movement is based on ideological aspects and based on political aspects. This includes da'wah, political support for Jokowi's opponents, and oppressive movements such as the 212 movements. FPI can strengthen identity politics because FPI often uses SARA issues in its movement as a radical Islamic organization.